2014
DOI: 10.1016/j.knee.2013.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Oblique coronal and oblique sagittal MRI for diagnosis of anterior cruciate ligament tears and evaluation of anterior cruciate ligament remnant tissue

Abstract: and showed a reasonable level of efficacy in detecting ACL remnant tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 16 publications
(3 reference statements)
1
24
0
Order By: Relevance
“…Our study showed that there is a higher interobserver agreement in diagnosis of complete and partial ACL tears using approaches B, C, and D in comparison to approach A, being highest with approaches C and D. This is in agreement with Kosaka et al, which showed higher diagnostic performance and interobserver agreement when using additional oblique coronal images [20]. The main reason for this is that oblique coronal images clearly delineate the course and femoral attachment of the ACL.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that there is a higher interobserver agreement in diagnosis of complete and partial ACL tears using approaches B, C, and D in comparison to approach A, being highest with approaches C and D. This is in agreement with Kosaka et al, which showed higher diagnostic performance and interobserver agreement when using additional oblique coronal images [20]. The main reason for this is that oblique coronal images clearly delineate the course and femoral attachment of the ACL.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, they conclude that the use of oblique MRI improved the accuracy of diagnosis of ACL [11]. According to previous studies, orthogonal MRI protocol and oblique-sagittal MRI were better than other oblique images; however, in this study, we found that using orthogonal sagittal and oblique coronal images show much better results than oblique sagittal images.…”
Section: Discussionmentioning
confidence: 47%
“…Tackling this issue, Kosaka et al demonstrated that a new method was not needed, as MRI accuracy can be increased by using a different view of knee lesions such as ACL injury. They found that the additional use of oblique MRI improved the accuracy of diagnosis of ACL tear [11]. Moreover, Nenezic et al showed that additional use of sagittal-oblique MRI has high accuracy for the evaluation of a complete rupture of the ACL.…”
Section: Introductionmentioning
confidence: 99%
“…First, ROI was evaluated using only sagittal MRI images rather than oblique coronal or oblique sagittal images, which have been reported to distinguish anteromedial and posterolateral bundles with greater accuracy. 32 In addition, it is relatively difficult to diagnose the small disruption of a proximally torn ACL that has adhered to the PCL or maintained gross alignment using a sagittal sequence. In such cases, axial or coronal plane images may allow a more accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%